Method for preparing monocyclic aromatic hydrocarbon from styrene derived waste plastics

By catalyzing the hydrogenation conversion of styrene-derived waste plastics under mild conditions, the problems of high temperature demand and high solvent cost in the prior art are solved, and efficient monocyclic aromatic hydrocarbon selectivity and environmentally friendly catalyst separation are achieved.

CN119552676APending Publication Date: 2025-03-04DALIAN UNIV OF TECH

Patent Information

Application Number
CN202411738089.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art has problems such as high temperature demand, high solvent cost, difficulty in product separation and self-polymerization of styrene in the chemical recycling of styrene-derived waste plastics, resulting in low reaction efficiency and high transportation costs.

Method used

Using a supported catalyst, the acid sites of the active metal and the support metal are used as the active center to achieve efficient hydrogenation conversion of styrene-derived waste plastic under mild conditions, selectively break the main chain C-C bond, avoid the hydrogenation of benzene ring, and retain the aromatic ring structure.

Benefits of technology

The high conversion rate of styrene-derived waste plastics and the high selectivity of monocyclic aromatic hydrocarbons are achieved, with the conversion rate reaching more than 90%, the selectivity of monocyclic aromatic hydrocarbons can reach 50%, and the catalyst is easy to separate, environmentally friendly and pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552676A_ABST
    Figure CN119552676A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of chemical recovery of waste plastics, and discloses a method for preparing monocyclic aromatic hydrocarbon from styrene derived waste plastics. A catalyst and waste plastics are uniformly mixed and then are loaded into a high-pressure reaction kettle, no extra solvent needs to be added, gas generated by the reaction is collected through a gas bag after the reaction is finished, and a liquid product and residual solids are centrifugally separated. In the method, the catalyst is simple to prepare, low in cost and good in stability, the styrene-derived waste plastics can be efficiently converted into monocyclic aromatic hydrocarbons such as methylbenzene and ethylbenzene under the solvent-free and mild conditions, and the conversion rate can reach 90% or above. According to the method, efficient chemical recovery of the styrene-derived waste plastics is realized, and a solution is provided for recovery and utilization of the styrene-derived waste plastics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of waste plastic recycling and relates to a method for preparing monocyclic aromatic hydrocarbons from styrene-derived waste plastics. Background Art

[0002] The annual output of plastics has increased exponentially from about 2 million tons in 1950 to 460 million tons in 2019. Plastics have many advantages, such as acid resistance, alkali resistance, oxidation resistance and excellent stability, but these advantages also lead to the problem that plastics are difficult to degrade. With the surge in plastic production, plastic pollution to the natural environment has become more serious. According to statistics, about 74 million tons of plastic waste are currently generated each year. According to forecasts, this figure will climb to 122 million tons per year by 2050. By efficiently recycling plastic waste, overall oil consumption and greenhouse gas emissions can be greatly reduced, and energy efficiency can be improved.

[0003] Polystyrene (PS) is a thermoplastic resin synthesized with styrene as the main raw material. It has the advantages of easy processing, good performance, low cost and good transparency. Commonly used polystyrene materials include ordinary polystyrene, expanded polystyrene (EPS), high impact polystyrene (HIPS) and syndiotactic polystyrene (SPS), etc., which are widely used in electronic appliances, building materials, packaging materials and daily necessities. As the fourth largest polyolefin plastic category after polyethylene, polypropylene and polyvinyl chloride, a type of plastic derived from styrene, such as ABS resin, styrene-butadiene copolymer, and styrene-isoprene copolymer, has many applications in the automotive industry. Styrene-derived waste plastics account for a large part of the total amount of plastic waste generated. And because of its small mass (especially the foamed type), it is difficult to transport and has high cost, resulting in low recycling value and is not easy to recycle. It is estimated that styrene-derived waste plastics account for up to 30% of the plastic waste in landfills, but only 1% of the waste can be effectively recycled.

[0004] There are currently four main technologies for recycling waste plastics, including energy recovery (incineration), primary (closed-loop) recycling, secondary (mechanical) recycling, and tertiary (chemical) recycling. In terms of energy recovery, incineration is a "waste-to-energy" method that converts plastics into heat and electricity. However, the energy obtained is far less than the energy required to prepare plastics, and the energy utilization efficiency is low. In terms of mechanical recycling, plastics are sorted, crushed, and then re-granulated, but this process will cause the destruction of the chain structure, causing a certain degree of change in molecular weight and molecular weight distribution, resulting in a decrease in the performance of secondary molding materials, limiting its application. Although chemical recycling is a promising strategy in polymer recycling, some obstacles still need to be overcome. Traditional polystyrene chemical recycling methods, such as catalytic pyrolysis, although this method can obtain a higher yield of styrene, but styrene is prone to self-polymerization during storage, difficult to store and transport, and the product contains other complex polycyclic hydrocarbons, the components are difficult to separate, reducing its usability. Catalytic hydrogenolysis can significantly reduce the reaction temperature and improve the selectivity of high-value products under the action of a catalyst, thereby achieving efficient utilization of waste plastics. However, it may lead to hydrogenation of the benzene ring in styrene-derived waste plastics, reducing reaction efficiency and product value, and a more efficient solution is needed.

[0005] Patent CN117295703A discloses a method for highly selectively recovering styrene monomer from polystyrene under certain conditions, wherein tetrahydrofuran is used as solvent and potassium bicarbonate is used as catalyst to recover styrene monomer by depolymerizing polystyrene in the presence of a catalyst, thereby achieving highly efficient recovery. However, the temperature required is relatively high, more solvent is added during the reaction, product separation is difficult, solvent cost is high, reaction efficiency is low, and styrene is prone to self-polymerization during transportation, resulting in high transportation cost. Summary of the invention

[0006] The present invention aims at the problem of chemical recycling of styrene-derived waste plastics and provides a method for preparing monocyclic aromatic hydrocarbons from styrene-derived waste plastics. In the reaction process, styrene-derived waste plastics can be efficiently catalytically hydrogenated and converted under mild conditions without adding additional solvents; the waste plastics conversion rate is high; the selectivity for monocyclic aromatic hydrocarbons is high; the main chain CC bond is selectively broken during the reaction; cyclohexane substitution byproducts of benzene ring hydrogenation are not generated; the aromatic rings are intact; and the monocyclic aromatic hydrocarbons can be extracted from the liquid after simple treatment. The catalyst preparation, reaction process and product extraction process are simple, providing a solution for efficient chemical recycling of styrene-derived waste plastics.

[0007] The technical solution of the present invention:

[0008] A method for preparing monocyclic aromatic hydrocarbons from styrene-derived waste plastics, wherein the prepared supported catalyst realizes efficient catalytic conversion of styrene-derived waste plastics to prepare monocyclic aromatic hydrocarbons, wherein the prepared catalyst is highly dispersed on a carrier, and the acid sites of the active metal and the carrier metal serve as active centers during the entire process, thereby realizing the gradual shearing of the polymer chain, the gradual shortening of the chain length, the selective breaking of the CC bond on the main chain, and avoiding excessive hydrogenation to form alkanes, thereby effectively retaining the aromatic ring structure. Under relatively mild reaction conditions, efficient conversion of styrene-derived waste plastics can be achieved, showing good selectivity for monocyclic aromatic hydrocarbons.

[0009] A method for preparing monocyclic aromatic hydrocarbons from styrene-derived waste plastics, comprising the following steps:

[0010] (1) dispersing the active metal salt and the carrier metal salt in deionized water, stirring at 25-60° C. to completely dissolve the solid to obtain an intermediate solution; uniformly impregnating the intermediate solution onto the template, calcining in air after completely drying, and reducing to obtain a catalyst;

[0011] (2) The catalyst and waste plastic are mixed evenly and then loaded into a high-pressure reactor without adding additional solvent. After the reaction is completed, the gas generated by the reaction is collected through an air bag, and the liquid product and the remaining solid are separated by centrifugation.

[0012] Preferably, in step (1), the active metal salt is one of ruthenium nitrosyl nitrate and cobalt nitrate; the carrier metal salt is aluminum nitrate; the mass ratio of the active metal salt to the carrier metal salt is 1:(100-150), and the concentration of the intermediate solution is 2-6 mol / L.

[0013] Preferably, the template in step (1) is one of C3N4, graphite, SBA-15, carbon black, MCM-41, and carbon nanotubes; and the mass ratio of the template to the intermediate solution is 1:(10-25).

[0014] Preferably, in step (1), the drying temperature is 80-100° C., the calcination temperature is 400-800° C., and the calcination time is 4-8 hours.

[0015] Preferably, the reduction temperature in step (1) is 500-750° C., and the reduction treatment time is 1-4 hours.

[0016] Preferably, in step (2), the mass ratio of the catalyst to the waste plastic is 0.05-0.5; the reaction temperature is 250-350° C.; the hydrogen pressure at room temperature is 0-4 MPa; and the reaction time is 2-16 hours.

[0017] Preferably, the waste plastic in step (2) is one or a mixture of two or more of polystyrene, ABS resin, styrene-butadiene copolymer, and styrene-isoprene copolymer.

[0018] Beneficial effects of the invention: The invention is used for catalytic conversion of styrene-derived waste plastics to prepare monocyclic aromatic hydrocarbons, has a high conversion rate and monocyclic aromatic hydrocarbon selectivity, does not undergo hydrogenation reaction on the benzene ring under long-term reaction and high hydrogen pressure, has a high aromatic ring retention rate, and the conversion rate can reach more than 90%, and the monocyclic aromatic hydrocarbon selectivity in its liquid product can reach 50%, and the product of the system is easy to separate and has high application value. The catalyst with excellent performance is prepared by selecting low-cost metals, the preparation process is simple, and kilogram-level preparation can be achieved; it is non-toxic, the catalyst performance is stable, it is easy to separate after the reaction, and it does not pollute the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is the XRD diffraction pattern of Co / Al2O3 and Al2O3.

[0020] Figure 2 The effect of different reaction pressures on the conversion of polystyrene catalyzed by Co / Al2O3.

[0021] Figure 3 Liquid NMR hydrogen spectra of Co / Al2O3-catalyzed polystyrene conversion at different reaction pressures.

[0022] Figure 4 The effect of different reaction times on the conversion of polystyrene catalyzed by Co / Al2O3.

[0023] Figure 5 Liquid NMR hydrogen spectra of Co / Al2O3-catalyzed polystyrene conversion at different reaction times.

[0024] Figure 6 This is the product distribution in the liquid of Co / Al2O3 at 300℃, 2 MPa hydrogen, and reaction time of 8 hours.

[0025] Figure 7 This is the liquid H NMR spectrum of Co / Al2O3 catalyzed polystyrene conversion using different preparation methods. DETAILED DESCRIPTION

[0026] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.

[0027] Example 1: Preparation of Co / Al2O3 Catalyst

[0028] Weigh 7.3555g of aluminum nitrate nonahydrate and 0.0499g of cobalt nitrate hexahydrate, add 12ml of deionized water and heat and stir until the nitrate is completely dissolved, weigh 6g of template, evenly impregnate the above mixed solution on the template, and then dry at 80°C for 12 hours to ensure that the moisture is completely removed. Subsequently, the dried mixed catalyst precursor powder is calcined at 700°C in an air atmosphere for 8 hours. Thereafter, the catalyst is reduced at 650°C in a hydrogen atmosphere for 2 hours. The theoretical loading of the catalyst metal obtained is 1wt%, and its XRD ray comparison diagram with Al2O3 is shown in Figure 1 .

[0029] Example 2: Investigating the effect of different metal loadings on catalyst performance

[0030] Weigh 7.355g of aluminum nitrate nonahydrate, add 12ml of deionized water and heat and stir until the aluminum nitrate is completely dissolved, then add 0.0397, 0.0499, and 0.1266g of cobalt nitrate hexahydrate respectively and stir evenly, then weigh 6g of template and evenly impregnate the template with the mixed solution. Then dry at 80°C for 12 hours. Subsequently, calcine the dried mixture at 700°C in an air atmosphere for 8 hours. Then reduce the catalyst at 650°C in a hydrogen atmosphere for 2 hours. The theoretical loading of the catalyst metal is 0.8wt%, 1wt%, and 2.5wt%.

[0031] Weigh 0.4g of the above catalysts with different metal loadings and 4.0g of polystyrene plastics, mix and load into a high-pressure reactor, and react for 8 hours under the reaction conditions of 2 MPa and 300°C. After the reaction is completed and cooled to room temperature, the gas phase product is collected with an air bag, and the generated liquid and catalyst are separated by centrifugation. The gas phase and liquid phase products are further analyzed by gas chromatography. The results show that the conversion rates are 82.25%, 96.16%, and 86.84%, respectively.

[0032] Example 3: Exploring the effects of different active metals on catalyst performance

[0033] Weigh 7.355g of aluminum nitrate nonahydrate, add 12ml of deionized water and heat and stir until the aluminum nitrate is completely dissolved, then add 1.710ml of ruthenium nitrate nitrate with a metal mass fraction of 1.5% and 0.0499g of cobalt nitrate respectively, weigh 6g of template, and evenly impregnate the above mixed solution on the template. Then dry at 80°C for 12 hours to ensure that the moisture is completely removed. Subsequently, the dried mixture is calcined at 700°C in an air atmosphere for 8 hours. After that, the catalyst is reduced in a hydrogen atmosphere at 650°C for 2 hours. The theoretical metal loading of the obtained catalyst is 1wt%.

[0034] 0.4 g of the above catalysts with different metal loadings were weighed and mixed with 4.0 g of polystyrene plastics and loaded into a high-pressure reactor. The reaction was carried out at 3 MPa and 300°C for 8 hours. After the reaction was completed and cooled to room temperature, the gas phase product was collected with an air bag, and the generated liquid and catalyst were separated by centrifugation. The gas phase and liquid phase products were further analyzed by gas chromatography. The results showed that the conversion rates were 97.12% and 95.15%, respectively.

[0035] Example 4: Investigating the effect of different calcination temperatures on catalyst performance

[0036] Weigh 7.355g of aluminum nitrate nonahydrate, add 12ml of deionized water and heat and stir until the aluminum nitrate is completely dissolved, then add 0.0499g of cobalt nitrate hexahydrate, stir evenly, and evenly impregnate the template with the mixed solution. Then dry at 80°C for 12 hours to ensure that the moisture is completely removed. Subsequently, the dried mixture is calcined at 650°C, 700°C, and 800°C in an air atmosphere for 8 hours. The catalyst is then treated in a hydrogen atmosphere at 650°C for 2 hours.

[0037] 0.4g of the above catalysts with different calcination temperatures were weighed and mixed with 4.0g of polystyrene plastics and loaded into a high-pressure reactor. The reaction was carried out at 2 MPa and 300°C for 8 hours. After the reaction was completed and cooled to room temperature, the gas phase product was collected with an air bag, and the generated liquid and catalyst were separated by centrifugation. The gas phase and liquid phase products were further analyzed by gas chromatography. The results showed that the conversion rates were 84.13%, 96.16%, and 85.62%, respectively.

[0038] Example 5: Investigating the effect of different reduction temperatures on catalyst performance

[0039] Weigh 7.355g of aluminum nitrate nonahydrate, add 12ml of deionized water and heat and stir until the aluminum nitrate is completely dissolved, then add 0.0499g of cobalt nitrate hexahydrate, stir evenly, and evenly impregnate the template with the mixed solution. Then dry at 80°C for 12 hours to ensure that the moisture is completely removed. Subsequently, the dried mixture is calcined at 700°C in an air atmosphere for 8 hours. The catalyst is then treated in a hydrogen atmosphere at 650°C, 700°C, and 750°C for 2 hours.

[0040] Weigh 0.4g of the above catalysts with different reduction temperatures and 4.0g of polystyrene plastics, mix and load into a high-pressure reactor, and react for 8 hours under the reaction conditions of 2 MPa and 300°C. After the reaction is completed and cooled to room temperature, the gas phase product is collected with an air bag, and the generated liquid and catalyst are separated by centrifugation. The gas phase and liquid phase products are further analyzed by gas chromatography. The results show that the conversion rates are 96.16%, 94.70%, and 89.04%, respectively.

[0041] Example 6: Investigating the effect of different reaction pressures on the conversion of polystyrene waste plastics catalyzed by catalysts

[0042] Weigh 0.4g of catalyst and 4.0g of polystyrene plastic respectively, mix them and put them into a high-pressure reactor, react at 300℃ for 8 hours, change the reaction pressure, and mainly explore the effects of 1.2 MPa, 2 MPa, 3 MPa and 4 MPa on the reaction. After the reaction is completed and cooled to room temperature, the gas phase product is collected with an air bag, and the generated liquid and catalyst are separated by centrifugation. The gas and liquid phase products are further analyzed by gas chromatography. The results show that the conversion rates are 75.76%, 96.16%, 95.15%, and 95.83%, respectively. For detailed results, see Figure 2 , Figure 3 .

[0043] Example 7: Investigating the effect of different reaction times on the conversion of polystyrene waste plastics by catalysts

[0044] Weigh 0.4g of catalyst and 4.0g of polystyrene plastic respectively, mix them and load them into a high-pressure reactor. The main purpose is to explore the effect of reaction time on the reaction. The reaction is carried out under the reaction conditions of 300°C and 3 MPa of hydrogen. The reaction time is changed to explore the effect of 4 hours, 8 hours, 12 hours, and 16 hours on the reaction. After the reaction is completed and cooled to room temperature, the gas phase product is collected with an air bag, and the generated liquid and catalyst are separated by centrifugation. The gas and liquid phase products are further analyzed by gas chromatography. The results show that the conversion rates are 86.11%, 95.15%, 95.42%, and 93.31%, respectively. For detailed results, see Figure 4 , Figure 5 .

[0045] Example 8: Investigating the effect of catalysts on the conversion of different polystyrene waste plastics

[0046] Weigh 0.4g of catalyst, 4.0g of polystyrene plastic cup and 4.0g of self-made monodistributed polystyrene respectively, mix and load into a high-pressure reactor, react under the reaction conditions of 300℃ and 3 MPa of hydrogen, change the reaction time,. After the reaction is finished and cooled to room temperature, the gas phase product is collected with an air bag, and the generated liquid and catalyst are separated by centrifugation. The gas phase and liquid phase products are further analyzed by gas chromatography. The results show that the conversion rate is 88.92% and 89.78%.

[0047] Example 9: Exploring the effects of different synthesis methods on the catalytic conversion of polystyrene waste plastics

[0048] Weigh 7.355g of aluminum nitrate nonahydrate, add 12ml of deionized water and heat and stir until the aluminum nitrate is completely dissolved, then add 0.0499g of cobalt nitrate hexahydrate, stir evenly, and hydroheat the mixed solution at 200℃ for 24 hours, filter, roast, and reduce. Weigh 0.4g of catalysts from different synthesis methods and 4.0g of polystyrene plastic and mix them into a high-pressure reactor. The main purpose is to explore the effects of different catalyst synthesis methods on the reaction. The reaction was carried out at 300℃ and 3 MPa of hydrogen. After the reaction was completed and cooled to room temperature, the gas phase product was collected with an air bag, and the generated liquid and catalyst were separated by centrifugation. The gas and liquid phase products were further analyzed by gas chromatography. The results showed that the conversion rates of the hard template method and the hydrothermal method were 95.15% and 12.10%, respectively. For detailed results, see Figure 7 .

Claims

1. A method for preparing monocyclic aromatic hydrocarbons from styrene-derived waste plastics, characterized in that: Here are the steps: (1) dispersing the active metal salt and the carrier metal salt in deionized water, stirring at 25-60° C. to completely dissolve the solid to obtain an intermediate solution; uniformly impregnating the intermediate solution onto the template, calcining in air after completely drying, and reducing to obtain a catalyst; (2) The catalyst and waste plastic are mixed evenly and then loaded into a high-pressure reactor without adding additional solvent. After the reaction is completed, the gas generated by the reaction is collected through an air bag, and the liquid product and the remaining solid are separated by centrifugation.

2. The method for preparing monocyclic aromatic hydrocarbons from styrene-derived waste plastics according to claim 1, characterized in that: In step (1), the active metal salt is one of ruthenium nitrosyl nitrate and cobalt nitrate; the carrier metal salt is aluminum nitrate; the mass ratio of the active metal salt to the carrier metal salt is 1:(100-150), and the concentration of the intermediate solution is 2-6 mol / L.

3. The method for preparing monocyclic aromatic hydrocarbons from styrene-derived waste plastics according to claim 1, characterized in that: In step (1), the template agent is one of C3N4, graphite, SBA-15, carbon black, MCM-41, and carbon nanotubes; and the mass ratio of the template agent to the intermediate solution is 1:(10-25).

4. The method for preparing monocyclic aromatic hydrocarbons from styrene-derived waste plastics according to claim 1, characterized in that: In step (1), the drying temperature is 80-100° C., the roasting temperature is 400-800° C., and the roasting time is 4-8 hours.

5. The method for preparing monocyclic aromatic hydrocarbons from styrene-derived waste plastics according to claim 1, characterized in that: In step (1), the reduction temperature is 500 to 750° C., and the reduction treatment time is 1 to 4 hours.

6. The method for preparing monocyclic aromatic hydrocarbons from styrene-derived waste plastics according to claim 1, characterized in that: In step (2), the mass ratio of the catalyst to the waste plastic is 0.05 to 0.5; the reaction temperature is 250 to 350° C.; the pressure of the hydrogen filled at room temperature is 0 to 4 MPa; and the reaction time is 2 to 16 hours.

7. The method for preparing monocyclic aromatic hydrocarbons from styrene-derived waste plastics according to claim 1, characterized in that: In step (2), the waste plastic is one or a mixture of two or more of polystyrene, ABS resin, styrene-butadiene copolymer, and styrene-isoprene copolymer.

Citation Information

Patent Citations

  • Method for recovering styrene monomer from waste polystyrene

    CN117295703A

Cited By

  • Application of Pt / CeO2 nanorod catalyst in self-hydrogen-supply hydrodepolymerization of waste polystyrene

    CN122558471A